2008
DOI: 10.2193/2007-039
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Breeding Mallards in the Great Lakes States

Abstract: Mallard (Anas platyrhynchos) populations in the United States portion of the Great Lakes region increased through the 1990s but have since declined. To promote sustainable growth of this population, managers need to understand how perturbation of vital rates will affect annual population growth rate (Λ). We developed a stage‐based model representing the female mallard population in the Great Lakes using vital rates generated from a landscape‐level study documenting reproductive parameters from 2001 to 2003. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 30 publications
3
57
2
Order By: Relevance
“…Coinciding with delayed irrigation (i.e., poor wetland conditions) in 2007, we captured fewer females, those captured were of lower body mass (x¯ in 2007 = 954 g; 2006 = 989 g), and they initiated fewer nests relatively later in the nesting season. Additionally, our renest rate was lower than reported for the Prairie Pothole and Great Lakes Regions (Coluccy et al , Arnold et al ). Renesting is most influenced by date of first nest attempt, which is related to body condition (Devries et al , Arnold et al ).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Coinciding with delayed irrigation (i.e., poor wetland conditions) in 2007, we captured fewer females, those captured were of lower body mass (x¯ in 2007 = 954 g; 2006 = 989 g), and they initiated fewer nests relatively later in the nesting season. Additionally, our renest rate was lower than reported for the Prairie Pothole and Great Lakes Regions (Coluccy et al , Arnold et al ). Renesting is most influenced by date of first nest attempt, which is related to body condition (Devries et al , Arnold et al ).…”
Section: Discussioncontrasting
confidence: 73%
“…Our estimate of breeding incidence (53%) in eastern Washington is considerably lower than values from the Prairie Parkland region of Canada (89%; Devries et al ); Ontario, Canada (96%; Hoekman et al a ); and the Great Lakes Region of the United States (84%; Coluccy et al ). Our overall estimate of breeding incidence is lower than that for first‐year females characterized as being in poor condition in the Prairie Parkland Region (60%; Devries et al ).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Patterns in habitat selection were consistent with previous research that identified use of woody or dense vegetative cover (McGilvrey , Sousa and Farmer , Smith and Flake , Granfors and Flake , Davis et al ). Brood and duckling survival may limit recruitment at our northern study area and additional data collection is required to support life‐cycle analysis (Coluccy et al , Davis et al ).…”
Section: Discussionmentioning
confidence: 99%
“…For species with precocial young, survival from hatching to fledging is a key factor influencing recruitment (Wisdom and Mills 1997, Hoekman et al 2002, Coluccy et al 2008). Prior to fledging, precocial young have relatively limited mobility compared with adults; thus, their survival is influenced by the landscape that was selected by adults during nesting Ratti 1992a, Krapu et al 2000).…”
Section: Introductionmentioning
confidence: 99%